The great challenges for Ecuadorian democracy in the post-COVID19 era - Paredes , Ana Marcela (2021)
Ana Marcela Paredes, one of the coordinators of this issue, interviews Manuel Alcántara Sáez. In the following interview, Professor Alcántara reflects on the challenges for democracy in the Ibero-American context. He discusses current ideas regarding the minimum consensus necessary for the post-COVID-19 era in countries such as Ecuador, which will have a new president and parliament in a few months. He takes a critical look at the major challenges facing Ecuadorian society, such as democracy fatigue, the use of technology for new forms of participation, and the proliferation of political organizations, which makes Ecuador the country with the most organizations of this type in the region. The fatigue of democracy to which he refers in several of his publications is the result of a series of changes in modern societies, in which the rapid development and dissemination of new information and communication technologies play a notable role, resulting in polarization, tensions, and demands among social and political actors.